Asuhan Keperawatan Pada Tn. T dengan Diagnosa Medis Post Operasi Soft Tissue Tumor (STT) Lengan Kanan di Ruang Mawar 2 RSUD Dr. Soeselo Kabupaten Tegal - Astrit Apriliana Putri; Ahmad Zakiudin; Yusriani Saleh Baso (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2025)
A tumor is a collection of abnormal cells that develop due to excessive and uncontrolled cell division (Angkotasan & Vioneery, 2022). Currently, tumors are considered one of the leading causes of morbidity and mortality worldwide (Maryati, 2023). The purpose of this study is to provide an in-depth understanding and description of nursing care for Mr. T, a patient with a medical diagnosis of post-operative soft tissue tumor (STT) in the right arm, who was treated in Room Mawar 2 at RSUD dr. Soeselo, Tegal Regency, in accordance with standardized nursing care guidelines. This study employed a descriptive case study method, with data obtained through interviews, observations, physical examinations, and documentation reviews. Based on the case analysis, the patient’s main complaint was severe pain following surgery. Three priority nursing diagnoses were identified: acute pain, knowledge deficit related to the disease and its management, and risk of infection due to post-surgical wound. Nursing interventions were planned and implemented according to SDKI (Standar Diagnosa Keperawatan Indonesia), SIKI (Standar Intervensi Keperawatan Indonesia), and SLKI (Standar Luaran Keperawatan Indonesia), adapted to the patient’s condition. The interventions included pain management techniques, health education, wound care, and infection prevention strategies. The results showed that after the nursing care was carried out, the patient reported a decrease in pain intensity, demonstrated increased knowledge regarding his condition, and exhibited no signs of infection. This study highlights the importance of systematic nursing care in post-operative soft tissue tumor patients to reduce complications, promote recovery, and improve quality of life. The findings are expected to contribute as a reference for nursing practice and further research on tumor management in clinical settings.